2012
DOI: 10.1007/s10067-012-1955-y
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon and plantar fascia in recently diagnosed type II diabetes: role of body mass index

Abstract: Previous research has shown that plantar fascia and Achilles tendon thickness is increased in diabetes. The aims of present study were to assess whether tendon changes can occur in the early stages of the disease and to evaluate the extent of the influence of body mass index (BMI). The study population included 51 recent-onset type II diabetic subjects, who were free from diabetic complications, divided according to BMI into three groups (normal weight, overweight, and obese). Eighteen non-diabetic, normal-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 21 publications
9
62
1
Order By: Relevance
“…Assessment by title and abstract excluded 1058 papers. Full text assessment of the remaining 135 reduced the yield to 33 papers 11 13–15 24 27 29–35 37–56. Reference list checking of these 33 papers identified a further two papers26 57 for inclusion, PubMed related articles identified one paper;23 citation tracking did not identify any papers.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment by title and abstract excluded 1058 papers. Full text assessment of the remaining 135 reduced the yield to 33 papers 11 13–15 24 27 29–35 37–56. Reference list checking of these 33 papers identified a further two papers26 57 for inclusion, PubMed related articles identified one paper;23 citation tracking did not identify any papers.…”
Section: Resultsmentioning
confidence: 99%
“…Our lack of difference in thickness between those with DM and controls mirrors a growing body of research which inconsistently finds thicker Achilles tendons in those with DM compared to controls. 17, 18, 38, 43-47 It is likely that changes in tendon size are impacted by more than presence or absence of DM. This is particularly true as we considered our a priori hypothesis regarding the posterior tibialis tendon and its relationship to deformity.…”
Section: Discussionmentioning
confidence: 99%
“…These subjects could definitely have had glucose intolerance or mild type 2 diabetes mellitus for a significant length of time before diabetes is diagnosed. [20] It was reported that patients with type 2 diabetes had greater impairments in mobility and more difficulties performing basic activities of daily living (ADL) than similarly aged nondiabetic persons. [21,22] This leads to loss of independence, and it may predict future hospitalization, institutionalization, and death.…”
Section: Discussionmentioning
confidence: 99%